Field investigation on the impact of vehicle traffic on the vibration of ancient seawalls in Qiantang River - Zhu, Shenming; Tu, Xiaobing; Hu, Min; Shi, Li; Zhou, Lei (Frontiers in Marine Science, 2023)
To investigate the vibrational impact of vehicular traffic on the ancient Qiantang River seawall, on-site measurements of the seawall's pulsation and forced vibrations under different vehicle speeds and axle loads were conducted. The acquired data were analyzed in the time domain, frequency domain, and 1/3 octave bands, revealing the time-frequency vibrational characteristics of the ancient seawall structure. The results indicate that the characteristic frequencies of the ancient seawall are 3 Hz and 10 Hz, with the primary frequency band of the structural vibrations induced by vehicular traffic ranging from 0 to 30 Hz. Vehicle traffic primarily caused vertical vibrations in the seawall structure, with along-dike horizontal vibrations being significantly higher than cross-dike vibrations. Based on the measurement results, an empirical relationship between the peak vibration velocity of the ancient seawall and variations in vehicle speed and axle load was established. It was found that, compared to axle load, increased vehicle speed had a more pronounced amplification effect on the structural vibrations of the ancient seawall. To ensure the vibrational safety of the ancient seawall relics, maximum vehicle speeds for different loading conditions of tri-axle trucks were provided based on vibration limits: for an axle load of 10 t, speeds should be below 34 km/h; for 11.52 t, below 24 km/h; for 13.04 t, below 20 km/h; and for 14.56 t, below 15 km/h.